Kuliah Kerja Nyata Menjunjung Tinggi Nilai Kearifan Lokal Menuju Nagari Berkemajuan - Novra, Eddi; Riyanda, Riko (PUAN INDONESIA, 2024)
This article discusses service activities carried out by KKN Implementing Agency Lecturers and Field Supervisors who collaborate to provide community service in the form of providing provision, training and empowerment to KKN students in order to contribute to the community in North Lintau Buo District. This activity has the theme Real Work Lectures Upholding the Value of Local Wisdom Towards a Progressive Nagari. The future achievement is that this service activity in the form of KKN can provide benefits to the surrounding community through the cross-study knowledge that students have obtained and then apply it for 40 days in the field.